Cykliny D v regulaci a dysregulaci buněčného cyklu u mnohočetného myelomu - Kubiczková, L; Dúcka, M; Sedlaříková, L; Kryukov, F; Hájek, R; Ševčíková, S (Klinicka onkologie, 2013)
Multiple myeloma is the second most common hematooncological disease characterized by clonal proliferation of plasma cells and monoclonal immunoglobulin production. It is a heterogenous disease; however, dysregulation of cyclins D seems to be an early unifying pathogenic event in multiple myeloma. In almost all patients, there is increased expression level of at least one of the cyclins D. Nevertheless, the mechanism of this increase is unknown in many cases. Next to wellknown roles of cyclins D in the cell cycle, they have many other functions contributing to tumor cell progression. Cyclins D are prognostic markers and are also used for subclassification of multiple myeloma. In this review, we focus on significance of cyclins D in multiple myeloma.
Keywords: proteiny buněčného cyklu; cyklin D; lidé; mnohočetný myelom; Multiple Myeloma; Cell Cycle Proteins; Disease Progression; progrese nemoci; Humans; multiple myeloma - cyclin D - pathogenesis - cell cycle regulation - TC groups; Cyclin D